Perception of Tinnitus: Direct and Indirect Effects of Resilience, Personality Traits, and Psychiatric Symptoms - Martins, Mariana L.; Galdino, Melyssa K.C.; Fernández-Calvo, Bernardino; Branco-Barreiro, Fátima C.A.; Fernandes, Thiago P.; da Rosa, Marine R.D. (Journal of the American Academy of Audiology, 2022)
Background Psychiatric conditions are common in individuals with tinnitus. Therefore, the ways individuals cope with such conditions and personality can influence the characteristics of tinnitus.Purpose The study aims to investigate the direct and indirect effects of resilience, personality traits, and psychiatric symptoms on the tinnitus perception.Research Design This is a descriptive, cross-sectional, and observational study involving quantitative results.Study Sample Thirty-seven individuals with chronic tinnitus (for more than 6 months) sought the tinnitus care service (mean age = 44.6 years; SD = 11.7 years).Data Collection and Analysis The specific anamnesis of tinnitus, adult self-report questionnaire, resilience scale, big five inventory, Tinnitus Handicap Inventory (M = 45.0; SD = 24.1), and visual analog scale (M = 6.4; SD = 2.7) were used. Psychoacoustic measurements (loudness: M = 25.4; SD = 12.8) of tinnitus were performed to characterize the condition in terms of pitch and loudness. The study analyzed the relationship between tinnitus (annoyance, severity, and loudness), psychiatric symptoms, personality, and resilience using multiple mediations.Results Resilience did not influence tinnitus severity (BCa: -1.12 to 0.51), annoyance (BCa: -0.10 to 0.11), or loudness (BCa: -0.44 to 0.28) when mediated by anxiety and depression. Additionally, there was only a direct effect of resilience for annoyance (t = - 2.14, p = 0.03; BCa: -0.10 to 0.11). There was no direct influence of anxiety and depression on the tinnitus severity (b = 0.53, p > 0.05), annoyance (b = - 0.01, p > 0.05), or loudness (b = 0.11, p > 0.05). However, there was an association of personality traits (neuroticism) with the tinnitus severity (b = 1.16, 95% CI: 0.15–2.17; t = 2.53, p = 0.02) and annoyance (b = 0.12, 95% CI: 0.003–0.24; t = 2.09, p = 0.04).Conclusion Resilience and psychiatric symptoms did not have a direct or indirect influence on the tinnitus annoyance, severity, or loudness. However with a direct association of resilience and annoyance, and neuroticism trait with the tinnitus annoyance and severity. Our results suggest that patients with chronic tinnitus and high neuroticism should receive personalized treatment.
Keywords: tinnitus; hearing; audiology; psychiatric disorders; anxiety; depression; neuroticism; personality